The Application of Nida’s Functional Equivalence Theory in the English Translation of Chinese Brands - Chao, Wang (Advances in Social Sciences Research Journal, 2025)
Translation is not only an art and a skill but also a science. Nida’s "functional equivalence" theory emphasizes communication through the transmission of information. It prioritizes "content over form," asserting that no translation achieves absolute equivalence. Translators, whether actively or passively, must consciously address the impact of cultural differences on translation, integrating emotions to convey the distinct cultures embedded in different languages. Functional equivalence provides direction for translation standards, constraining translators’ free interpretation and reducing deviations between the target and source languages. This ensures that the target language conveys the original message clearly and acceptably across different linguistic forms.